Thyroglobulin measurement in fine‐needle aspiration biopsy of metastatic lymph nodes after rhTSH stimulation. Issue 1 (20th June 2011) - Cappelli, Carlo; Pirola, Ilenia; De Martino, Elvira; Gandossi, Elena; Cimino, Elena; Samoni, Francesca; Agosti, Barbara; Rosei, Enrico Agabiti; Casella, Claudio; Castellano, Maurizio
Abstract: Background: Thyroglobulin measurement in the washout of the needle used in fine‐needle aspiration cytology (FNAC) has been proposed for the early detection of lymph node metastasis both in patients with or without serum thyroglobulin antibodies; however, up to now, there have been no reports that recombinant human thyrotropin (rhTSH) stimulation modifies thyroglobulin measurement in lymph node aspirates. Methods: We described, after rhTSH stimulation, the switching from undetectable to detectable levels of thyroglobulin in fine‐needle aspiration fluid from a suspected metastatic lymph node in 2 patients. Results: We hypothesized that thyroglobulin levels in the lymph node increased after rhTSH stimulation. The excess thyroglobulin saturates all thyroglobulin antibody binding sites and becomes detectable, explaining why it was undetectable when TSH was suppressed. Conclusion: On the basis of our experience, we suggest submitting to thyroglobulin measurement in the washout of the needle used in FNAC all patients with detectable serum thyroglobulin antibody after rhTSH stimulation. © 2011 Wiley Periodicals, Inc. Head Neck, 2013